ANALISIS MATURITY LEVEL DALAM BLENDED LEARNING PADA DOMAIN SERVICE OPERATION FRAMEWORK ITIL V3 - Shofwan Hanief; I Wayan Jepriana (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTAlong with the development of technology, we are currently in the era of industrial revolution 4.0, where in this era computing is carried out in an obscene way by relying on internet technology. Higher education is one of the institutions that also plays an important role is a very suitable institution to participate in the 4.0 industrial revolution. with the speed of internet access that is already such and the dependence of the community on technology, especially the communication technology, provides an opportunity and a positive impact on the teaching and learning process. The learning process carried out on one of the Introduction to Information Technology courses at STIKOM Bali is the course in which the learning process is done with the blended learning learning model. The learning process is done face to face and uses online learning media. The lecture mechanism is designed in accordance with the academic calendar and material content is made uniform with multimedia animation, so that one class with another class has the same understanding. Related to the use of information and communication technology media in blended learning, it is necessary to manage technology so that the use of information and communication technology used can be measured. ITIL (Information Technology Infrastructure Lybrary) V3. This study focuses on the measurement of information and communication technology in the PTI subjects using blended learning learning models. In this measurement using a maturity level scale, where the instrument used is a questionnaire. For the preparation of the questionnaire and distribution using Google docs. The results of this study are in the form of a maturity level in the domain service operation of the ITIL V3 framework and recommendations of measurements that have been made.Keywords: blended learning, governance, ITIL Versi 3, maturity levelABSTRAKSeiring dengan perkembangan teknologi, saat ini kita sedang berada pada era revolusi industry 4.0, dimana pada era ini komputasi dilakukan secara obiquitas dengan mengandalkan teknologi internet. Perguruan tinggi merupakan salah satu lembaga yang juga berperan penting merupakan lembaga yang sangat cocok untuk ikut serta masuk dalam revolusi industry 4.0. dengan kecepatan akses internet yang sudah demikian rupa dan ketergantungan masyarakat terhadap teknologi khususnya tekmologi komunikasi memberikan suatu peluang dan dampak positif dalam proses belajar mengajar. Proses pmbelajaran yang dilakukan terhadap salah satu matakuliah Pengantar Teknologi Informasi di STIKOM Bali adalah matakuliah yang proses pembelajaranannya dilakukan dengan model pembelajaran blended learning.proses pembelajaran dilakukan dengan cara tatap muka dan menggunakan media online learning. Mekanisme perkuliahan dirancang sesuai dengan kalender akademik dan konten-konten materi dibuat seragam dengan animasi multimedia, sehingga antara satu kelas dengan kelas yang lainnya mempunyai pemahaman yang sama. Terkait dengan penggunaan media teknologi informasi dan komunikasi pada pembelajaran blended learning ini, maka perlu sebuah pengelolaan teknologi agar pemanfaatan teknologi informasi dan komunikasi yang digunakan dapat terukur. ITIL (Information Technology Infrastructur Lybrary) V3. Penelitian ini menitikberatkan kepada pengukuran terhadap teknologi informasi dan komunikasi pada matakuliah PTI yang menggunakan model pembelajaran dengan blended learning. Dalam pengukuran ini menggunakan skala maturity level, dimana instrument yang digunakan adalah kuesioner. Untuk penyusunan kuesioner dan pendistribusiannya menggunakan google docs. Hasil dari penelitian ini berupa maturity level pada domain service operation framework ITIL V3 dan rekomendasi dari pengukuran yang telah dilakukan.Kata kunci : blended learning, tatakelola, ITIL Versi3, maturity level